2015
DOI: 10.1016/j.neubiorev.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation stress hypothesis of environmental enrichment

Abstract: One hallmark of psychiatric conditions is the vast continuum of individual differences in susceptibility vs. resilience resulting from the interaction of genetic and environmental factors. The environmental enrichment paradigm is an animal model that is useful for studying a range of psychiatric conditions, including protective phenotypes in addiction and depression models. The major question is how environmental enrichment, a non-drug and non-surgical manipulation, can produce such robust individual differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
114
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(132 citation statements)
references
References 184 publications
(274 reference statements)
12
114
0
6
Order By: Relevance
“…We found that stress differentially affected behavior depending on the animals' housing background and the specific behavior scrutinized. Altogether, our findings with respect to anxiety and aggression are congruent with the recently postulated inoculation stress hypothesis [39]. This hypothesis claims that particular chronic mild stress, such as stress that originates from living in a complex social environment, can protect against subsequent stressors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that stress differentially affected behavior depending on the animals' housing background and the specific behavior scrutinized. Altogether, our findings with respect to anxiety and aggression are congruent with the recently postulated inoculation stress hypothesis [39]. This hypothesis claims that particular chronic mild stress, such as stress that originates from living in a complex social environment, can protect against subsequent stressors.…”
Section: Discussionsupporting
confidence: 90%
“…Environmental enrichment has been suggested to be the functional inverse of stress [38] but SEEs can simultaneously parallel the endocrine, neurobiological, behavioral and physiological aspects of stress [39]. Thus, it is not clear whether SEEs would intensify the effects of stress on behavior or whether this type of housing would buffer the effects of external stressors.…”
Section: Discussionmentioning
confidence: 99%
“…61 The protective effects of EE may also partially result from the inoculation stress hypothesis, put forth by Crofton and colleagues (2015), which briefly posits that mild stress associated with living in a complex setting and interacting with conspecifics in a non-aggressive manner "inoculates" the rats against consequent stressors and/or drugs of abuse. 62 This theory could certainly be extrapolated to explain the EE-related attenuation of HAL-induced detrimental effects observed in the current study.…”
Section: Journal Of Neurotraumamentioning
confidence: 68%
“…According to the match/ mismatch hypothesis and inoculation stress hypotheses, early life enrichment may serve as a mild stressor that causes biological adaptations to optimally prepare, or “inoculate” the organism for coping with subsequent stress exposure (Crofton, Zhang, & Green, 2015, Schmidt, 2011). Future studies are required to examine whether enrichment and/or concurrent stress and enrichment can block or attenuate chronic stress-related behavioral disruptions later in life.…”
Section: Discussionmentioning
confidence: 99%